Logistic system and value chain trade: case of Central Asia - Shomurodov Tokhir Boymurod ugli (Zien Journals, 2022)
The globalization of the world economy and the internationalization of business open up the possibility for most enterprises to search for more optimal sources of supply for production and marketing of their products. Today, many enterprises have enough resources and opportunities to organize and carry out transportation, not only in the domestic market, but also in the external one, using transit mechanisms. Taking into account global trends, companies are not limited only by the capabilities of the region of presence and national borders, but are constantly looking for new opportunities to cover the planned need for resources and the ability to meet the growing demand in foreign markets. In this regard, the design of global supply chains is inextricably linked with the movement of traffic flows and the implementation of related transport tasks
Keywords: globalization; internationalization; global trends; chains